Den kloge godsforvalter (Luk 16,1-8a): jødisk pagtsnomisme som nøgle til lignelsen i Lukasevangeliets fortælleforløb - Larsen, Kasper Bro (Dansk teologisk tidsskrift, 2017)
Resumé The parable of the prudent manager in Luke 16:1–8a constitutes an exegetical puzzle. The present article understands the parable in light of early Jewish covenantal nomism (E.P. Sanders). The parable is not a theological replica of “The Prodigal Son” (pace J.R. Donahue) but a sequel to that story. Whereas “The Prodigal Son” tells a story to outsiders of getting in, “The Prudent Manager” narrates to insiders a story about staying in. The manager first foolishly squanders his master’s possessions (v. 1b–3); but in the face of crisis, he acts generously in the interest ofothers (vv. 4–7) and is praised for being prudent (v. 8a). The manager thus personifies “the faithful and prudent manager” mentioned in Luke 12:43. He is an example for disciples to follow. Occasioned by the 75th anniversary of academic theology at Aarhus University, the article begins with a review of 20th century dialectical-theological applications of the parable in the works of Professors K.E. Løgstrup, Regin Prenter, P.G. Lindhardt, and Johannes Sløk.